Light Scattering Reviews, Vol. 6 Light Scattering and Remote Sensing of Atmosphere and Surface - Kokhanovsky, Alexander A. (Springer eBooks, 2012)
This is the next volume in series of Light Scattering Reviews. Volumes 1-5 have already been printed by Springer. The volume is composed of several papers ( usually, 10) of leading researchers in the respective field. The main focus of this book is light scattering, radiative transfer and optics of snow.